Implementing (un)fair procedures: containing favoritism when unequal outcomes are inevitable - Schmidt, Robert J.; Trautmann, Stefan T. (The journal of law, economics, and organization, 2023)
We study the selection of people when unequal payoffs are inevitable, but fair procedures are feasible, as in selecting one person from several candidates for a job. We show that allocators may be influenced by their similarity with a recipient, leading to favoritism in outcomes. We study four interventions to reduce favoritism and induce fair procedures, without restricting the allocator’s decisions: transparency of the allocation process; a private randomization device; allowing the allocator to delegate to a public randomization device; and allowing the allocator to avoid information about recipients. Making use of beliefs and fairness judgments, we show why some interventions work, while others do not (JEL D63, J16, J7, C92).
Online veröffentlicht: 7. Oktober 2021
Gesehen am 27.10.2021
Keywords: Aufsatz in Zeitschrift